Remembering the personal past descriptions of autobiographical memory - Ross, Bruce M. (Oxford University Press, 1991)
The impetus for this book is the belief that a comprehensive description of autobiographical memory in both form and function must be an interdisciplinary endeavour. The author examines motivation and emotion as components of human memory and assembles sources previously ignored by psychologists.